The Effectiveness of Distribution of Zakat Funds by BAZNAZ in Batu Bara Regency through the Smart Coal Program as an Effort to Improve Education and Coal Community Development - Zsasa Aulia Hubara; Muhammad Yafiz (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Zakat is an obligation that must be carried out for all Muslims. Carrying out zakat is an obligation for all Muslims. With zakat, poor people can get welfare in terms of material and spiritual. The function of education is very important for humans because it not only educates the nation but also improves the quality of life. In the role of the education function, something important in human life, this means that every individual has the right to and hopes to always develop in education which is always associated with increasing human resources. BAZNAS Batu Bara Regency has a Smart Coal program, namely distributing zakat aid funds for education with the aim that the Batu Bara community gets educational assistance funds for their children who are continuing their education. This study used descriptive qualitative method . The purpose and benefits of the research as a result of the internship carried out by the author is to find out the extent of the role of Baznaz in Batu Bara Regency in improving education as an effort for community growth in Batu Bara Regency. From the results of the study, it can be concluded that from the amount of zakat and infaq receipts in 2022, the distribution for education is only about 13.49% per year.